Biotransformação do inseticida Flubendiamida por fungos de solo e Lacase: análise dos metabólitos por espectrometria de massas (LC-MS/MS) - Yada Junior, George Mitsuo (2016)
The high consumption of pesticides in Brazil has led to public concern about their disposal, contamination and accumulation in the environment. Flubendiamide, N2 - [1,1- dimethyl-2- (methylsulfonyl) ethyl] - 3- iodo-N1-[2 methyl-4-[1,2,2,2-tetrafluoro-1-(trifluoromethyl)ethyl]phenyl]-1,2-benzenedicarboxamide is toxicologically classified as persistent to the environment (class III) and also toxic to microcrustaceans. This study mainly aimed to: selecting fungi isolated from soil by growth inhibition test using Belt and Actara insecticides; analyze the flubendiamide biotransformation product by soil fungi isolated, by Botryosphaeria rhodina MAMB-05 and by the laccase enzyme fungi; and evaluete if Belt®, Actara® and flubendiamide Bayer standard ® insecticides act as laccase inducers. The growth inhibition test was on solid medium PDA with the fungi isolated from soil and with B. rhodina. This fungus and those which showed the best growth results were conducted to the flubendiamide biotransformation experiment, together with the laccase extract of the fungus B. rhodina.The metabolites were assessed by LC-MS / MS. Determination of laccase activity was measured using ABTS as substrate. The result of the inhibition test emphasizes the growth of JUSOLCL039 and JUANT070 fungi. In addition to B. rhodina MAMB-05, biotransformation experiment detected 47 metabolites. The metabolic route from ion m / z 587 by the fungus MAMB-05 was proposed, through loss of iodine and hydroxylation reaction. The metabolite m / z 663 was found in the extract of JUANT070 fungi and in the laccase extract. The metabolic route suggested a dehalogenation reaction of fluoride, following by its confirmation through Tandem mass spectrometry. The metabolite m / z 697 formed by the hydroxylation reaction was identified in the laccase enzyme extract. The results showed metabolites which were formed by the laccase enzyme, or by JUANT070, JUSOLCL039 and B.rhodina other enzymes. These fungi were shown to be constitutive producers of laccase in the presence of the insecticide Actara, Belt and the analytical standard flubendiamide. However, these insecticides demonstrated not act as laccase inducers for the three fungi.